Determination of diflufenican and azaconazole pesticides in wastewater samples by GC-MS after preconcentration with stearic acid functionalized magnetic nanoparticles-based dispersive solid-phase extraction - Metin, Berfin; Guleryuz, Aybuke; Chormey, Dotse Selali; Zaman, Buse Tugba; Bakirdere, Sezgin (SPRINGER, 2023)
This study presents the preconcentration of diflufenican and azaconazole from domestic wastewater samples by using dispersive solid-phase extraction (dSPE) for determination by gas chromatography-mass spectrometry (GC-MS). Stearic acid-coated magnetic nanoparticles were used as adsorbents for dSPE method. In order to maximize the efficiency of the extraction process, parameters such as magnetic nanoparticle (MNP) type and amount, eluent type and volume, mixing type, and mixing period were all optimized. The linear range obtained for azaconazole and diflufenican was 7.50-500 ng/mL and 7.50-750 ng/mL, and their limits of detection/quantification (LOD/LOQ) were calculated as 1.3/4.3 ng/mL and 1.4/4.7 ng/mL, respectively. By comparing the LOD values of direct GC-MS and the developed dSPE method, azaconazole and diflufenican recorded approximately 35 and 38 folds enhancement in detection power. Recovery experiments with domestic wastewater were carried out to certify the proposed method's accuracy and applicability. By using the matrix matching calibration strategy, the good percent recovery results between 98 and 105% were obtained.
Keywords: Azaconazole; Diflufenican; Dispersive solid-phase extraction; Gas chromatography-mass spectrometry; Stearic acid-coated magnetic nanoparticles; Pesticides; RESIDUE ANALYSIS; HPLC-MS; CHROMATOGRAPHY; SPECTROMETRY; FRUITS; Environmental Sciences & Ecology